Main policies actions for development of Costa Rican Atlantic/Caribbean and Chorotega regions: comparison between intentions and final results. 1950-2009. - Blanco Obando, Edgar Eduardo (2022)
This article analyzes the main state actions aimed at development of production systems in Costa Rica´s regions Atlantic/Caribbean and Chorotega, and expansion of key services for population. Through reviewing numerous official, statistical, scientific and technical documents, it´s shown that Costa Rican State has directed significant and continuous investment to incorporate regions into national economic model and ensure access to essential services. However, these actions have not been enough to reverse regional conditions of poverty and inequality.